PELAKSANAAN PROGRAM TAHFIZH AL-QUR’AN DI SDIT MA’ARIF PADANG PANJANG - Mukhlis, Mukhlis (El -Hekam, 2019)
The purpose of this research is to be analyse how performing program tahfizh Al Qur ’an at SDIT Ma ’arif Padang Panjang, and to analyse supporting and resistor factor in performing programs tahfizh Al Qur ’ an at SDIT Ma ’arif Padang Panjang. Method that is utilized in this research is kualitatif's method, utilizing analisis's approaching descriptive. This research is done at SDIT Ma ’arif  Padang Panjang, one that as data source in observational it is learn tahfizh and class student IV., V and VI one constitutes key and headmaster informan as data of supporting. In data collecting tech utilizes observation, interview and documentation. Meanwhile tech tests data authenticity utilize triangulation. menunjukan's observational result that tahfizh Qur's learning performing ’ an at SDIT Ma ’arif Padang Panjang gets guidance on syllabus already being made by coherent Islamic School Network (JSIT Centers), with minimal memorizing limitation student is 3 juz.